1998
DOI: 10.1038/3123
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan for human obesity genes reveals a major susceptibility locus on chromosome 10

Abstract: Obesity, a common multifactorial disorder, is a major risk factor for type 2 diabetes, hypertension and coronary heart disease (CHD). According to the definition of the World Health Organization (WHO), approximately 6-10% of the population in Westernized countries are considered obese. Epidemiological studies have shown that 30-70% of the variation in body weight may be attributable to genetic factors. To date, two genome-wide scans using different obesity-related quantitative traits have provided candidate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
246
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(275 citation statements)
references
References 25 publications
25
246
4
Order By: Relevance
“…This study provides substantial evidence for linkage supporting QTLs previously reported to be linked to serum leptin and plasma adiponectin levels. The linkage region on chromosome 2 in this study (with the peak at 72.6 cM for PBF) overlaps with the region found to be linked to leptin in several studies [14][15][16] and with the region linked to plasma adiponectin by Comuzzie et al 17 The linkage regions identified on chromosome 4 and 5 have not previously been reported as harboring QTLs influencing obesity phenotypes. Yet, the relatively strong linkage signals observed in this study suggest that these genomic regions may indeed contain QTLs influencing obesity traits.…”
Section: Discussionsupporting
confidence: 81%
“…This study provides substantial evidence for linkage supporting QTLs previously reported to be linked to serum leptin and plasma adiponectin levels. The linkage region on chromosome 2 in this study (with the peak at 72.6 cM for PBF) overlaps with the region found to be linked to leptin in several studies [14][15][16] and with the region linked to plasma adiponectin by Comuzzie et al 17 The linkage regions identified on chromosome 4 and 5 have not previously been reported as harboring QTLs influencing obesity phenotypes. Yet, the relatively strong linkage signals observed in this study suggest that these genomic regions may indeed contain QTLs influencing obesity traits.…”
Section: Discussionsupporting
confidence: 81%
“…Early reports indicated relatively consistent findings for 10p from three studies of US European American, French, and German cohorts. [19][20][21]63 Subsequently, several other reports on obesity-related phenotypes have found signals in the same or nearby chromosomal regions, but also including signals on 1q, 12 12,27 None of these studies have reported sex-specific linkage findings.…”
Section: Discussionmentioning
confidence: 99%
“…5 The POMC gene maps to chromosome 2p23.3. 6 A major quantitative trait locus (QTL) determining leptin levels has been linked to the POMC region in Mexican American families 7 and replicated in two other studies, 8,9 suggesting that variation in body mass index (BMI) or fat mass in the population might be linked to functional variant(s) in POMC coding or regulatory sequences.…”
Section: Introductionmentioning
confidence: 99%